Geographic variation in sex‐chromosome differentiation in the common frog (Rana temporaria). Issue 14 (28th June 2014) - Rodrigues, Nicolas; Merilä, Juha; Patrelle, Cécile; Perrin, Nicolas
Abstract In sharp contrast with birds and mammals, sex‐determination systems in ectothermic vertebrates are often highly dynamic and sometimes multifactorial. Both environmental and genetic effects have been documented in common frogs (Rana temporaria). One genetic linkage group, mapping to the largest pair of chromosomes and harbouring the candidate sex‐determining gene Dmrt1, associates with sex in several populations throughout Europe, but association varies both within and among populations. Here, we show that sex association at this linkage group differs among populations along a 1500‐km transect across Sweden. Genetic differentiation between sexes is strongest (FST = 0.152) in a northern‐boreal population, where male‐specific alleles and heterozygote excesses (FIS = −0.418 in males, +0.025 in females) testify to a male‐heterogametic system and lack of X‐Y recombination. In the southernmost population (nemoral climate), in contrast, sexes share the same alleles at the same frequencies (FST = 0.007 between sexes), suggesting unrestricted recombination. Other populations show intermediate levels of sex differentiation, with males falling in two categories: some cluster with females, while others display male‐specific Y haplotypes. This polymorphism may result from differences between populations in the patterns of X‐Y recombination, co‐option of an alternative sex‐chromosome pair, or a mixed sex‐determination system where maleness is controlled either by genes or by environment depending on populations or families. We propose approaches to test among these alternative models, to disentangle the effects of climate and phylogeography on the latitudinal trend, and to sort out how this polymorphism relates to the 'sexual races' described in common frogs in the 1930s.